Experiencing That Life Is Divine through the Science of Creative Intelligence: A Qualitative Analysis of Results of Research in Consciousness - Yin, Chan Man (International Journal of Multidisciplinary in Management and Tourism, 2020)
Experiences of the divinity of life, being lived as a daily reality of particular individuals, have been recorded throughout the ages. This paper is a qualitative phenomenological case study of self-research, presenting the results of my research in consciousness, on the divinity of life as a daily reality, correlated with the principles of Maharishi Science of Creative IntelligenceSM. Maharishi Science of Creative Intelligenceis the science of consciousness that provides both theoretical understanding and practical,systematic technologies for anyone to research anddevelop higher states of consciousness.The technologies are the Transcendental Meditationâ technique and the TM-Sidhiâ program. The principles of Maharishi Science of Creative Intelligence describe signposts ofgrowth towardexperiencing the divinity of life as a daily reality, described as the highest state of consciousness, Unity Consciousness. Qualitative analysis of the research results is made in terms of the principles of Maharishi Science of Creative Intelligence relevant to growth of Unity Consciousness. The results of this research in consciousness document that the divinity of life is experienced in the field of Transcendental Consciousness and that repeated experience of Transcendental Consciousness leads to the divinity of life being lived as a daily reality, suggesting growth toward Unity Consciousness.